2D hydrogen-bonded organic frameworks: in-site generation and subsequent exfoliation. Issue 48 (19th May 2021) - Luo, Yang-Hui; Zhang, Lan; Fang, Wen-Xia; Ma, Shu-Hua; Dong, Hui; Su, Shan; Zheng, Zi-Yue; Li, Di-Ning; Zhai, Li-Hai
Abstract : By using in situ generated formate, 2D HOFs with square-like TCPP-HCO2 grid sheets have been obtained, the sheets can be well preserved in the single-layer limit with efficient photocatalytic activity in aqueous system. Abstract : By using in-site generated formate, 2D HOFs of TCPP, with excellent stability and permanent porosity (BET surface area larger than 560 m 2 g −1 ), have been obtained. The constructed 2D square-like TCPP-HCO2 grid sheets have shown considerable in-plane stability that comparable to the TCPP-based 2D MOFs, that can be exfoliated into atomically thin 2D nanosheets with efficient photocatalytic activity in aqueous system. These results are expected to shed light on the application-orientated one-pot synthesis for new kinds of multi-dimensional HOFs.